Detection and Tracking of Face Location in the Pre-processing Stage of Recognition of Micro Expressions Using the Kanade-Lucas-Tomasi (KLT) Method - Priska Choirina; Ulla Delfana Rosiani (Jurnal Informatika Polinema, 2020)
Research and observation of micro-expression movements requires a careful pre-processing stage, because it is associated with observing subtle movements and very fast durations. At this stage, the detection and tracking of the face area must always be precise so that the observation of movement in the face area can be accurate. Several video samples of the micro expression dataset showed facial movements followed by small movements of the head. The movements outside the movement in this facial area will affect the performance of the micro expression recognition system. This study detects and tracks the location of faces during micro-expression movements. The Viola-Jones method is used for face detection and the Kanade Lucas Tomasi (KLT) method for tracking feature points. After the face is detected correctly, a point tracking is performed at the tip of the nose. This tracking of the movements at the nose tip is followed by the formation of the facial area. So that the face area will always be in the right position even if there is movement in the head. The test and testing data used in this study were the CASME II dataset. The test from this research shows that the detection and tracking of facial areas can be done precisely and accurately on all test data. It is hoped that with the formation of facial areas that are always precisely tracked, the next process of recognition of micro expressions can run well.